One-Dimensional Hydrodynamic Modelling for River Flood Forecasting - Yusron Saadi (Institute of Research and Community Outreach - Petra Christian University, 2008)
The ability to forecast maximum water depth during maximum discharge of a design flood is very important in designing flood protection scheme along the river reach. This paper explains the use of ISIS Flow, a one-dimensional hydrodinamic computer modelling for river flood forecasting. The computer simulations produced detailed information from each node including the maximum water depth during maximum discharge, thus it can be expected that an economical flood protection structure can be produced.